International Migration and the Propagation of HIV in Sub- Saharan Africa - Frédéric Docquier; Chrysovalantis Vasilakis; D. Tamfutu Munsi (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
In this paper, we identify and quantify the role of international migration in the propagation of HIV across sub-Saharan African countries. We use panel data on bilateral migration flows and HIV prevalence rates covering 44 countries after 1990. Controlling for unobserved heterogeneity, reverse causality, reflection issues, incorrect treatment of country fixed effects and spatial auto-correlation, we find evidence of a highly robust emigration-induced propagation mechanism. On the contrary, immigration has no significant effect. Numerical experiments reveal that the long-run effect of emigration accounts for more than 4 percent of the number of HIV cases in 15 countries (and more than 20 percent in 6 countries).
Keywords: F22; I12; J61; 330